Analisa Penutupan Lahan ( Land Cover ) Kota Palembang Berbasis Sistem Informasi Geografis - Ienda Meiriska (JURNAL PATANI: Pengembangan Teknologi Informasi dan Pertanian, 2020)
This analysis aims to find out the amount of land cover change in Palembang City, where Palembang is one of the cities undergoing land change. The change in land cover is an event of shifting the type of land cover from one species to another followed by increasing and decreasing use over time or changing the function of a land at different times. In Palembang City there are several examples of changing land like paddy fields, and green open spaces. Paddy fields are agricultural farms that are physically flat surfaces, limited by bunds, and can be planted with rice, palawija or other cultivated crops. Most paddy fields are used for cultivation which are classified into 4 types namely technical irrigation, semi technical, simple and rain-fed. Meanwhile, green open spaces are elongated / lane and / or clustered areas, which prefer open, growing plants, either naturally grown and divided into 2 types: natural green open spaces and artificial green open spaces. In this analysis the data used are secondary data satellite map map of 2014 which resulted from Badan Pembangunan dan Pendapatan Daerah (BAPPEDA) Kota Palembang The method used in this analysis is the Natural Break (Jenks) method with emphasis on the color difference of each type of land cover.